(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article is devoted the problem of sexual education and sexual socialization of children of preschool age in Germany. It is exposed the specific of the use offacilities ofmediaeducation in elucidative work fram sen ual education in preschool educational establishments of Germany.